(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
This study aimed to explore the relationship between breast shape measurements and breast beauty assessment. Breast Beauty Subjective Assessment System (BBSAS) was developed to evaluate the beauty of breasts. 75 female subjects aged 20-39 years were selected for assessment from the anthropometric database of BIFT-Aimer Human Engineering Research Centre. 43 females working in intimate apparel design were chosen as judges to answer a five-scale questionnaire using the BBSAS. 66 detailed measurements especially related to the breast region were also taken for investigation. Data analysis results indicated that the breast beauty score was highly correlated with breast side view profile and breast erectness. Beautiful breasts selected by judges had the following common characteristics: the ratio of bust height to whole body height was 0.71; a triangle was constructed by front neck point, right bust point and left bust point was an isosceles triangle with the top angle less than 60°. The regression equation to predict the breast beauty scale was obtained based on key breast measurements. This study provides a new knowledge on relationship between the breast shape and breast beauty, as well as some useful guidelines for bra design.